Economic Analysis of Groundnut Production in Andhra Pradesh - Sunandini, G. P.; Devi, Irugu Shakuntala (International Journal of Economic Plants, 2020)
For the study on cost of cultivation of groundnut crop in Andhra Pradesh, the data was obtained from Directorate of Economics and Statistics, Ministry of Agriculture, Government of India. The cost of cultivation was found to be Rs. 55142.26. Among the operational costs, labour cost accounted to a major share of 60%, indicating the labour intensive nature of groundnut cultivation. The cost of cultivation and the gross returns analysed during the two periods noted that cost of cultivation (C2) increased by 40% where as A2+FL increased by 52% against the increase of 25% in the gross returns. The cost of production was higher in Andhra Pradesh than other major groundnut producing states Gujarat and Tamil Nadu. The cost of cultivation needs to be reduced by opting good management practices and more mechanization so as to make groundnut cultivation profitable in Andhra Pradesh.